2008
DOI: 10.1088/1478-3975/5/2/026001
|View full text |Cite
|
Sign up to set email alerts
|

Discrete breathers in protein structures

Abstract: Recently, using a numerical surface cooling approach, we have shown that highly energetic discrete breathers (DBs) can form in the stiffest parts of nonlinear network models of large protein structures. In the present study, using an analytical approach, we extend our previous results to low-energy discrete breathers as well as to smaller proteins. We confirm and further scrutinize the striking site selectiveness of energy localization in the presence of spatial disorder. In particular, we find that, as a shee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
144
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(156 citation statements)
references
References 66 publications
12
144
0
Order By: Relevance
“…2). An analysis of the low-frequency modes (3)(4)(5)(6)(7)(8)(9)(10) shows that the correlations were mostly consistent with the non-homologous b-sheet ensemble; however, there are regions where there is disagreement (Supplementary Figs 3 and 4) due to contributions of overtones of the fundamental mode frequencies. Despite the disagreement in some regions of the b-sheet, regions of agreement were found in many of the first 10 normal modes, as identified by the alternating checkerboard pattern of positive and negative dihedral correlations.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…2). An analysis of the low-frequency modes (3)(4)(5)(6)(7)(8)(9)(10) shows that the correlations were mostly consistent with the non-homologous b-sheet ensemble; however, there are regions where there is disagreement (Supplementary Figs 3 and 4) due to contributions of overtones of the fundamental mode frequencies. Despite the disagreement in some regions of the b-sheet, regions of agreement were found in many of the first 10 normal modes, as identified by the alternating checkerboard pattern of positive and negative dihedral correlations.…”
Section: Resultsmentioning
confidence: 90%
“…The existence of channels of correlated motions is implicitly required as the inter-atomic interactions that govern them decay rapidly with distance 2 . While the mechanisms that cause these behaviours are still largely unknown, recent progress has been made in the study of the allostery of enzymes that contain a central b-sheet, where weakly correlated motions link interaction sites 3,4 and store energy for preparation for binding and catalysis 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, we have shown that spatially localized bandedge normal modes (NM) can be continued from low energies to DB solutions centered at the same sites as the corresponding NMs (the NM sites). Note that the latter lie, as a rule, within the stiffest regions of a protein [33,39]. More generally, however, DBs display a gap in their excitation spectrum.…”
Section: Introductionmentioning
confidence: 90%
“…This process is accompanied by large structural rearrangements if there is an energy exchange between protein regions with "discrete breathers" (localized excitations). [28][29][30][31] The conformational selection paradigm implies that "discrete breathers" should be located close to ligand-binding sites. Although at first sight, the conformational selection paradigm and the approach that we used in this study look different, the similarity between them becomes clear if we make an analogy between "discrete breathers" and the eigenmodes of the burial mode model energy function 12 -in both descriptions, ligand-binding suppresses one mode and stimulates another, coupling large scale motions to the transduction of small forces.…”
Section: Discussionmentioning
confidence: 99%